The role of renin-angiotensin system in patients with left ventricular assist devices. (October 2020) - Briasoulis, Alexandros; Ruiz Duque, Ernesto; Mouselimis, Dimitrios; Tsarouchas, Anastasios; Bakogiannis, Constantinos; Alvarez, Paulino
End-stage heart failure is a condition in which the up-regulation of the systemic and local renin-angiotensin-aldosterone system (RAAS) leads to end-organ damage and is largely irreversible despite optimal medication. Left ventricular assist devices (LVADs) can downregulate RAAS activation by unloading the left ventricle and increasing the cardiac output translating into a better end-organ perfusion improving survival. However, the absence of pulsatility brought about by continuous-flow devices may variably trigger RAAS activation depending on left ventricular (LV) intrinsic contractility, the design and speed of the pump device. Moreover, the concept of myocardial recovery is being tested in clinical trials and in this setting LVAD support combined with intense RAAS inhibition can promote recovery and ensure maintenance of LV function after explantation. Blood pressure control on LVAD recipients is key to avoiding complications as gastrointestinal bleeding, pump thrombosis and stroke. Furthermore, emerging data highlight the role of RAAS antagonists as prevention of arteriovenous malformations that lead to gastrointestinal bleeds. Future studies should focus on the role of angiotensin receptor inhibitors in preventing myocardial fibrosis in patients with LVADs and examine in greater details the target blood pressure for these patients.